Islamic Religious Education Innovation for Preventing Bullying in Higher Education: Inovasi Pendidikan Agama Islam untuk Mencegah Perundungan di Perguruan Tinggi - Wardi , Muhammad Musfiatul; Mappanyompa, Mappanyompa (Universitas Muhammadiyah Sidoarjo, 2025)
Bullying in higher education is a problem that often goes unnoticed, even though it has a serious impact on students' mental health and academic climate. Islamic Religious Education has great potential in shaping character and preventing deviant behavior, but its role in the context of bullying prevention has not been studied in depth. Therefore, this study aims to describe the role of Islamic Religious Education in preventing bullying in higher education. Using a descriptive qualitative approach, this research explores students' experiences, perceptions, and attitudes towards learning Islamic Religious Education as an effort to build religious and social character. The research informants amounted to 15 Islamic Religious Education lecturers, and 97 students from three faculties at Muhammadiyah Mataram University, selected through purposive sampling technique to represent the diversity of academic backgrounds. Data were collected through semi-structured interviews, classroom observations, and review of current scientific literature (2018-2024). Data analysis used the Miles and Huberman interactive model, through data reduction, data presentation, and conclusion drawing. The results showed that Islamic Religious Education learning that integrates Islamic values, religious moderation approach, and participatory methods are able to raise students' awareness of the importance of tolerance, empathy, and justice. The internalization of these values plays a significant role in shaping inclusive social behavior and reducing the potential for bullying. Data validity is strengthened through source triangulation, while reliability is maintained with a systematic audit trail. The findings recommend strengthening the Islamic Religious Education curriculum based on anti-bullying values as part of the student character building strategy in higher education. Highlights: Islamic Education Shapes Character – It fosters tolerance, empathy, and justice to reduce bullying. Participatory and Moderation-Based Methods – Effective in promoting inclusive social behavior among students. Curriculum Enhancement Needed – Recommends integrating anti-bullying values into Islamic Religious Education. Keywords: Islamic Religious Education, Bullying, Student, Character, Religious Moderation